2021
DOI: 10.3138/jammi-2021-0009
|View full text |Cite
|
Sign up to set email alerts
|

Jamestown Canyon and snowshoe hare virus seroprevalence in New Brunswick

Abstract: Background: Jamestown Canyon virus (JCV) and snowshoe hare virus (SSHV) are wide-ranging mosquito-borne arboviruses in the California serogroup viruses (CSGV) that are known to circulate in New Brunswick. Despite potential for debilitating central nervous system manifestations, the prevalence of human exposure to these viruses in New Brunswick is unknown. The goal of this study was to quantify rates of human exposure in New Brunswick to these neglected arboviruses. Methods: A retrospective, anonymized provinci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 16 publications
0
12
0
Order By: Relevance
“…Urbanization and international travel, for example, heighten transmission risks and the (re)introduction of mosquito-borne diseases (MBDs) 3 , 4 . In Canada, endemic pathogens like West Nile virus, eastern equine encephalitis virus, and California serogroup viruses (CSGv) are on the rise 3 , 5 , 6 . Some studies have demonstrated CSGv prevalence in mosquitoes, animals, and humans 5 8 , including a 2018–2019 MBD surveillance program in Southeastern Ontario, Canada, which identified several CSGv-positive mosquito pools.…”
Section: Introductionmentioning
confidence: 99%
“…Urbanization and international travel, for example, heighten transmission risks and the (re)introduction of mosquito-borne diseases (MBDs) 3 , 4 . In Canada, endemic pathogens like West Nile virus, eastern equine encephalitis virus, and California serogroup viruses (CSGv) are on the rise 3 , 5 , 6 . Some studies have demonstrated CSGv prevalence in mosquitoes, animals, and humans 5 8 , including a 2018–2019 MBD surveillance program in Southeastern Ontario, Canada, which identified several CSGv-positive mosquito pools.…”
Section: Introductionmentioning
confidence: 99%
“…Over 22 states have reported human cases, presumed to be locally acquired (CDC ArboNET 2022). Reports of JCV antibody prevalence in humans range from 4% to >20% across North America from southwestern US National Parks to New Brunswick, CA (Mayo et al 2001, Kosoy et al 2016, Mincer et al 2021). However, human case reporting and mosquito vector surveillance are not uniformly conducted across the United States.…”
Section: Introductionmentioning
confidence: 99%
“…Antibodies increased with age in studies that analyzed this variable, suggesting long-term endemic transmission of JCV within these communities (Walters et al 1999, Patriquin et al 2018, Mincer et al 2021). Seropositivity was statistically higher in males in 3 surveys (Grimstad et al 1986a, Patriquin et al 2018, Mincer et al 2021) but there was no difference among sexes in native populations from Alaska (Walters et al 1999). Although reported clinical cases are rare, serological evidence suggests that residents are frequently exposed to JCV and that most infections are mild or asymptomatic.…”
Section: Disease Patternsmentioning
confidence: 98%
“…Underlying symptomatic cases is a much larger population of exposed individuals as revealed by serosurveys of human populations. Seropositivity to JCV among humans was reported at 28% in Michigan (Grimstad et al 1986a), 4–10% in CT (Mayo et al 2001), 18% in Alaska (Walters et al 1999), 9–24% in Quebec (Sampasa-Kanyinga et al 2013), 21% in Nova Scotia (Patriquin et al 2018), and 27% in New Brunswick (Mincer et al 2021). Antibodies increased with age in studies that analyzed this variable, suggesting long-term endemic transmission of JCV within these communities (Walters et al 1999, Patriquin et al 2018, Mincer et al 2021).…”
Section: Disease Patternsmentioning
confidence: 99%
See 1 more Smart Citation